2016
DOI: 10.1016/j.reprotox.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of maternal polymorphisms in arsenic (+3 oxidation state)-methyltransferase AS3MT and fetal sex in relation to arsenic metabolism and infant birth outcomes: Implications for risk analysis

Abstract: Arsenic (+3 oxidation state) methyltransferase (AS3MT) is the key enzyme in the metabolism of inorganic arsenic (iAs). Polymorphisms of AS3MT influence adverse health effects in adults, but little is known about their role in iAs metabolism in pregnant women and infants. The relationships between seven single nucleotide polymorphisms (SNPs) in AS3MT and urinary concentrations of iAs and its methylated metabolites were assessed in mother-infant pairs of the Biomarkers of Exposure to ARsenic (BEAR) cohort. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 55 publications
4
9
0
Order By: Relevance
“…). The AS3MT minor allele frequencies in this population were similar to previously published studies from Mexico [Drobná et al, ], Bangladesh [Engström et al, ], and Mongolia [Chen et al, ] (Fig. ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…). The AS3MT minor allele frequencies in this population were similar to previously published studies from Mexico [Drobná et al, ], Bangladesh [Engström et al, ], and Mongolia [Chen et al, ] (Fig. ).…”
Section: Resultssupporting
confidence: 90%
“…A more recent in vitro investigation confirmed that N6AMT1 is involved in MMA III methylation, but its effects were secondary to AS3MT [Zhang et al, 2015]. Although several epidemiology studies have found associations between AS3MT polymorphisms and the proportion of MMA in urine [Engstr€ om et al, 2011[Engstr€ om et al, , 2007Pierce et al, 2012;Drobn a et al, 2016], few have examined cancer risk in the same study population [Chung et al, 2009;Engstr€ om et al, 2015], and only two have assessed the role of N6AMT1 polymorphisms in arsenic metabolism [Harari et al, 2013;Chen et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory response in women pregnant with a male infant was much more robust than that observed in women pregnant with a female infant. These results provide molecular support for previous research demonstrating that iAs-associated diseases may be more severe in male infants and children that experience in utero iAs exposure [10,14,49]. The genes identified as differentially expressed in association with urinary arsenic species were also significantly associated with birth outcomes, namely gestational age, birth weight, birth length, and ponderal index.…”
Section: Discussionsupporting
confidence: 86%
“…This highlights that women pregnant with male infants may experience a more robust inflammatory response to iAs exposure. This is supported by research demonstrating that males may experience greater risk of certain diseases associated with prenatal iAs exposure compared to females [14,23,49]. These differentially expressed genes are involved in Toll-like receptor signaling and tumor necrosis factor (TNF) production.…”
Section: Discussionmentioning
confidence: 92%
“…However, in Maine, exposure to drinking water levels greater than only 5 μg/L iAs is associated with a decrease of 5–6 Full Scale IQ, Verbal Comprehension, Working Memory, and Perceptual Reasoning IQ points in children 27 . The disparity in these results may be related to several factors, including (1) nutritional differences between these populations 76 , (2) potential differences in susceptibility between populations with respect to the particular effects of iAs 77 , and possibly (3) difficulties in quantifying and comparing neurodevelopmental indicators, such as IQ, between culturally different populations. The differences between the magnitude of these effects and possible underlying factors represent the challenge presented by identifying the critical dose ranges for iAs-associated health outcomes.…”
Section: Discussionmentioning
confidence: 99%